SOLID SOLUTIONS WITH ENERGETICALLY NONEQUIVALENT SUBLATTICES AS SOURCE OF INFORMATION ON RATE OF POSTCRYSTALLIZATION COOLING OF MINERALS - Akimov V.V.; Abramovich M.G. (My University, 1988)
The distribution of atoms in lattices of minerals such as alkali feldspars or orthopyroxenes have long been used to estimate the temperature of natural processes. We describe an approach to determining the kinetics of postcrystallization colling of minerals based on evaluation of the time-dependent relations. As an example we consider triclinic albite with one ordering parameter. However, our method can also be applied to crystals with several ordering parameters. Our approach allows one to employ data on mineral crystals with energetically nonequivalent positions in the lattice as 'geospeedometers' and to introduce corrections to the kinetics of the rock cooling in estimating the temperatures of mineral genesis.